Phosphorus Use Efficiency in Canola Genotypes - Kürşat Korkmaz; Çağatay Altıntaş (Turkish Journal of Agriculture: Food Science and Technology, 2016)
Phosphorus (P) deficiency is a widespread macronutrient deficiency and is one of the major constraints limiting canola production. Efficient P fertilizer method’s is important for economic production of canola and sustaining of environmental quality. The aim of this research is to investigate P use efficiency (PUE) of canola genotypes at an early growth stage. The experiment was set up as a completely randomized design in a factorial scheme. The factors were ten canola genotypes (Excalibur, Nelson, Vectra, Orkan, Triangel, TKK08-5, Oase, Elvis, Es Hydromel and Licord) and three P rates (0, 50 and 100 mg kg-1). The plant parameters, dry weight of shoot and root varies significantly with P levels in all applications. In general, P concentrations and dry weight of the genotypes are linearly raised by P treatments. The genotype Elvis produced significantly higher shoot dry matter 9.24 g pot-1 at 100 mg kg-1 P rate compared to the other applications. However, without P, dry matter (DM) of genotypes varied between 1.67 to 6.96 g pot-1. Cultivars classified as efficient responsive are: Elvis, inefficient responsive: Nelson, Orkan, Oase, Licord, and efficient nonresponsive: Excalibur, Vectra, Triangel, TKK08-5, Es Hydromel. Plant dry matter can be used for identification of the genotypes which could be adapted to low or high soil P availability conditions at an early growth stage. Nutrient use efficiency and genotypic differences in plants should be considered in order to create an accurate and a balanced fertilizer program as well as improving crop yield in agricultural production system.